Lactose Intolerance in Bulgaria: A Preliminary Study - Chengolova Z.; Ivanova R.; Shentov P.; Levterova V. (Acta Medica Bulgarica)
Lactose intolerance affects more than 65% of the world’s population. Main methods for confirming this condition include hydrogen breath test, oral lactose administration and blood glucose measurements, and also biopsy. An association of lactose intolerance with genetic polymorphisms specific to certain regions is found. In Europe, genetic testing of C/ T13910 is being implemented. Incidence data is available for most countries in Europe. At the time of our study, there is no data on the prevalence of lactose intolerance in Bulgaria. In this study, a questionnaire on the prevalence and awareness of lactose intolerance among the Bulgarian population was created. For the first time, the results of a lactose tolerance test and a genetic test of volunteers have been reported and systematized. The lactose test with oral administration of lactose was designed for self-testing and appeared to be a good choice to establish the current condition but was not definite enough. As many as 45% showed inconclusive results, and the patient’s symptoms were the leading point for the diagnosis. The genetic test results showed a huge prevalence of the recessive allele (C13910) associated with lactose intolerance (97%). New horizons are being opened for studies of the Bulgarian population to establish their lactose resistance in the presence of the recessive allele.